Analisis Struktur Dan Desain Holder Plate - Erick Sandi Prabowo (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The holder plate is a crucial component in manufacturing mechanical systems, serving as a support and load-bearing element. This study aims to analyze the structure and design of the holder plate using the Finite Element Method (FEM) approach with SolidWorks software. The material used is 1100 series aluminum alloy. Simulations were performed to determine the distribution of stress, strain, displacement, and safety factor. The results show that the holder plate design has a maximum stress of 2.933 MPa, a maximum strain of 3.979e-11, a maximum displacement of 3.21e-09 mm, and a safety factor of 12. The design is categorized as safe because the stress value is still far below the material's yield strength.Keywords: Holder plate, 1100 series aluminum, SolidWorks, deformation, safety factor. Abstrak Holder plate merupakan komponen penting dalam sistem mekanik manufaktur yang berfungsi sebagai penopang dan penahan beban. Penelitian ini bertujuan untuk menganalisis struktur dan desain holder plate ,menggunakan pendekatan Finite Element Method (FEM) dengan perangkat lunak SolidWorks. Material yang digunakan adalah aluminium alloy seri 1100. Simulasi dilakukan untuk mengetahui distribusi tegangan, regangan, perpindahan, dan faktor keamanan. Hasil menunjukkan bahwa desain holder plate memiliki tegangan maksimum sebesar 2,933 MPa, regangan maksimum 3,979e-11, displacement maksimum 3,21e-09 mm, dan faktor keamanan sebesar 12. Desain dikategorikan aman karena nilai tegangan masih jauh di bawah yield strength material.Kata kunci: Holder plate, Alimunium seri 1100, SolidWorks, deformasi, faktor keamanan.